PENGARUH PROMOSI DAN HARGA JUAL SMARTPHONE MEREK OPPO F11 TERHADAP KEPUTUSAN PEMBELIAN - HAYANI HAYANI (Jurnal Manajemen Bisnis Unbara, 2020)
With the tittle effect of promotion and sell price of Oppo F11 smartphone on purchasing decisions (case study on the customer of Oppo F11 smartphone in the Jelita Lahat shop. This study aims to determine the effect of promotion on purchasing decisions, sell price of Oppo F11 smartphone on purchasing decisions, promotion and sell price of Oppo F11 smartphone on purchasing decisions in the Jelita Lahat shop. The sample in this study amounted to 78 respondents. The sampling technique uses the Accidental Sampling methode. Regression equation Y = 4,372 + 0,574 X1 + 0,325 X2 + e. Based on statistical data analysis, indicators in the study are valid and reliable. The sequence individually from each the variable most affects is the variable promotion with a regression coefficient of 0,574 then the sell price variable with a regression coefficient of 0,325. Obtained tcalculated the variable promotion (X1) of 7,654 > 1,992 and the sell price variable (X2) obtained of 3,505 > 1,992. This means that tcalculated is greater than ttable then H0 rejected and H1 accepted. Retrieved calculated F value of 50,845 > 3,12 so that it can be concluded that there are significant simultaneously (together) beetwen the promotion (X1) and sell price (X2) on purchasing decisions (Y).